2015
DOI: 10.1128/jcm.03288-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enzyme Immunoassays and Real-Time PCR for Detecting Shiga Toxin-Producing Escherichia coli in Southern Alberta, Canada

Abstract: c Two immunoassays (Shiga Toxin Chek and Shiga Toxin Quik Chek) and real-time PCR were used to detect Shiga toxin-producing Escherichia coli. For enriched culture, the sensitivity and specificity of the three methods ranged from 80.0% to 98.2% and 98.0% to 100.0%, respectively. STEC isolates were identified in 2.6% of the 784 samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…High specificity is important for assays targeting diseases with low prevalence rates, such as those caused by STEC; a specificity of <99% has a detrimental effect on the positive predictive value. Our values of 100% sensitivity and 100% specificity with direct testing of fecal samples are higher than those reported recently by other groups for the STQC (25, 26). However, the two previous studies used a real-time PCR assay as the reference method instead of a Vero cell cytotoxicity assay, and expression of Shiga toxin genes was not confirmed.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…High specificity is important for assays targeting diseases with low prevalence rates, such as those caused by STEC; a specificity of <99% has a detrimental effect on the positive predictive value. Our values of 100% sensitivity and 100% specificity with direct testing of fecal samples are higher than those reported recently by other groups for the STQC (25, 26). However, the two previous studies used a real-time PCR assay as the reference method instead of a Vero cell cytotoxicity assay, and expression of Shiga toxin genes was not confirmed.…”
Section: Discussioncontrasting
confidence: 66%
“…Using different culture conditions, including mitomycin C induction, however, Beutin et al were able to detect with their Vero cell assay toxin produced by strain EH250, suggesting, as we have also observed, that toxin production varies depending upon broth type, inducing agent, and culture conditions (20). Recently, two independent groups (25, 26) reported that the STQC was unable to detect all described Shiga toxin subtypes. In both of those studies, however, the immunoassay results were compared to those of a real-time PCR assay and toxin production was not verified by Vero cell assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Stx, as a common trait of all STEC strains, is considered as target molecule for diagnostic and therapeutic purposes. Currently, many rapid detection strategies, including polymerase chain reaction (PCR) for detection of stx genes and immuno‐assays for detection of Stx protein, have been widely used . PCR is specific and sensitive, but it heavily depends on laboratory facility and experienced personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many rapid detection strategies, including polymerase chain reaction (PCR) for detection of stx genes and immuno-assays for detection of Stx protein, have been widely used. [13][14][15] PCR is specific and sensitive, but it heavily depends on laboratory facility and experienced personnel. Sometimes false-negative results are obtained due to the PCR inhibitors in the fecal samples, [14] or the total clearance of intestinal floras including STEC with excessive use of antibiotics prior to diagnosis.…”
Section: Introductionmentioning
confidence: 99%